2014
DOI: 10.1155/2014/787153
|View full text |Cite
|
Sign up to set email alerts
|

Camellia sinensis (L.) Kuntze Extract Ameliorates Chronic Ethanol‐Induced Hepatotoxicity in Albino Rats

Abstract: The goal of this study was to investigate the hepatoprotective effects of aqueous extract of Camellia sinensis or green tea extract (AQGTE) in chronic ethanol-induced albino rats. All animals were divided into 4 groups in the study for a 5-week duration. 50% ethanol was given orally to the rats with two doses (5 mg/kg bw and 10 mg/kg bw) of AQGTE. Ethanol administration caused a significant increase in the levels of plasma and serum enzymatic markers, alanine aminotransferase (ALT), aspartate aminotransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
5
16
0
Order By: Relevance
“…Previous investigations showed increased hepatic GST activity in rats with NAFLD (Hardwick et al, 2010;Lodhi et al, 2014), which comes in support to our results (Table 3). Interestingly, total serum GST activity declines in conditions of oxidative stress but it should be mentioned that there are several isoforms of GST.…”
Section: Discussionsupporting
confidence: 93%
“…Previous investigations showed increased hepatic GST activity in rats with NAFLD (Hardwick et al, 2010;Lodhi et al, 2014), which comes in support to our results (Table 3). Interestingly, total serum GST activity declines in conditions of oxidative stress but it should be mentioned that there are several isoforms of GST.…”
Section: Discussionsupporting
confidence: 93%
“…In one study, polychlorinated biphenyls induced hepatotoxicity associated with increase in LDL, triglycerides and cholesterol after 30 days of continuous treatment [63] . Several authors have observed a pattern of increased lipid profile in response to drug induced liver toxicity [55] , [40] . The reason for an increase in lipid profile, during liver damage for e .…”
Section: Discussionmentioning
confidence: 99%
“…The green tea exerts improvement in liver function by preventing the production of reactive oxygen species (ROS) and enhancing the antioxidant defense system capacity. Thus green tea extract has protective effects against ethanol toxicity (Lodhi et al, 2014). …”
Section: Camellia Sinensis (Green Tea)mentioning
confidence: 99%